A method for preparing a sustainable microbial fuel cell material
By using biocarbon coated carbon felt as an anode material and metal-doped chitosan microspheres as cathode materials in microbial fuel cells, the problem of low production capacity of existing electrode materials is solved, efficient battery operation and voltage output is achieved, and environmentally friendly applications are supported.
Patent Information
- Application Number
- CN202311364715.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The electrode materials of existing microbial fuel cells are low in production capacity and expensive, which limits their development and application.
By preparing biocarbons coated on the surface of the carbon felt, as anode material, and using metal-doped chitosan microspheres as the cathode material, an efficient microbial fuel cell electrode material is formed.
It improves the power production performance of microbial fuel cells, realizes independent operation of the battery, and significantly improves voltage output, supporting environmentally friendly and pollution-free natural delivery.
Smart Images

Figure CN117457917B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field, and in particular relates to a method for preparing a sustainable microbial fuel cell material. Background Art
[0002] Microbial fuel cells (MFCs) are a green and environmentally friendly bioreactor with the dual functions of electricity generation and organic pollutant degradation. That is, microorganisms are used as catalysts to directly degrade organic pollutants to obtain electricity. Its working principle is that the electrogenic bacteria in the anode chamber degrade organic matter to release electrons and protons. The electrons pass through the electrode via the external circuit to the cathode, and the protons pass through the ion exchange membrane to the cathode. The two combine with the electron acceptor to form water. MFCs play an obvious role in solving the water resource crisis and environmental pollution, but most conventional electrode materials have low production capacity and are expensive, which greatly limits the development and application of MFCs. Biochar has good biocompatibility and is conducive to the attachment of microorganisms. The present invention improves the electricity generation performance of the electrode material by preparing biochar and coating it on the surface of carbon felt. The prepared electrode material is applied to dual-chamber MFCs, the electrochemical performance is compared, and a good coating morphology is determined. It is applied to MFCs, and multiple reactors are combined in series / parallel to explore the increase of current and voltage, providing practical guidance for engineering applications.
[0003] At present, the research on microbial fuel cells is still in the laboratory exploration stage and has not been directly applied in practice. Therefore, it is of great significance to develop MFCs devices that can be directly applied in practice and ensure their sustainable and stable operation. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a microbial fuel cell material.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a microbial fuel cell material, comprising:
[0008] preparing positive electrode materials;
[0009] preparing negative electrode materials;
[0010] The positive electrode material, the mixed solution and the negative electrode material are connected in series in the order of positive electrode, mixed solution, negative electrode or in the completely opposite order to form a circuit, thereby obtaining the electrode material of the microbial fuel cell.
[0011] As a preferred embodiment of the preparation method of the present invention, the mixed solution is a water-oil mixed solution prepared by mixing an organic solution, a polymer and an oil phase.
[0012] As a preferred embodiment of the preparation method of the present invention, the mixed solution is a metal-doped chitosan mixed solution prepared by mixing water, acetic acid, chitosan, ferroferric oxide and copper oxide, which is mixed in an oil phase mixed solution prepared by mixing liquid paraffin and Span 80 and stirred evenly to prepare a water-oil phase mixed solution.
[0013] As a preferred embodiment of the preparation method described in the present invention, the positive electrode and the negative electrode are pretreated carbon felt, and the pretreatment is to soak the carbon felt in a hydrogen peroxide solution, and then soak it in hydrochloric acid after washing, and wash it until it returns to neutrality.
[0014] As a preferred embodiment of the preparation method of the present invention, the positive electrode material is prepared by coating N nanopowder on the positive electrode material.
[0015] As a preferred solution of the preparation method described in the present invention, the cathode material is metal-doped chitosan microspheres.
[0016] As a preferred embodiment of the preparation method of the present invention, the cathode material comprises chitosan, ferroferric oxide and copper oxide, and the mass ratio of chitosan, ferroferric oxide and copper oxide is 1:1:1.
[0017] As a preferred embodiment of the preparation method of the present invention, the microbial fuel cell device is maintained at an ambient temperature of 30-35°C.
[0018] Another object of the present invention is to overcome the deficiencies in the prior art and provide a microbial fuel cell material.
[0019] Another object of the present invention is to overcome the deficiencies in the prior art and provide an application of a microbial fuel cell material, characterized in that the microbial fuel cell device is used for sewage treatment.
[0020] Beneficial effects of the present invention:
[0021] (1) The anode is coated with N nanopowder and the cathode is coated with metal-doped chitosan microspheres, both of which can improve the power generation performance of microbial fuel cells.
[0022] (2) Realize the independent operation of the microbial fuel cell and light up the light bulb, preparing for the subsequent environmentally friendly and pollution-free natural release. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0024] Figure 1 It is the electrochemical performance test diagram of cathode material;
[0025] Figure 2 It is the electrochemical performance test diagram of the anode material;
[0026] Figure 3 It is a microbial fuel cell reactor;
[0027] Figure 4 It is carbonized metal-doped chitosan microspheres;
[0028] Figure 5 This is a photo of a light bulb lit by the microbial fuel cell made in the present invention. DETAILED DESCRIPTION
[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0031] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0032] Example 1
[0033] This embodiment is used to perform pretreatment of carbon felt and measure the performance after pretreatment:
[0034] Pretreatment of carbon felt:
[0035] The carbon felt was soaked in a hydrogen peroxide solution (10%, 90°C) for 3 hours, washed and soaked in a hydrochloric acid solution (10%, 90°C) for 1 hour, then rinsed thoroughly with deionized water until the solution was neutral, dried at 60°C, and cut into different sizes for later use.
[0036] The pretreated carbon felt was cut into 2×4cm, 2×5cm, 2×6cm, 3×4cm, 3×5cm, and 3×6cm. They were coated with metal-doped chitosan cathode materials and dried. They were immersed in cathode liquid and their electrochemical properties, including CV curves, LSV, and Tafel, were measured using an electrochemical workstation. The results are shown in Figure 2. Figure 1 .
[0037] Example 2
[0038] (1) Pretreatment: Natural dandelion seeds (produced in Hebei Province, with high protein content) were soaked in acetone for 6 h to remove impurities such as surface oil and other dirt. They were then washed three times with deionized water and dried in a vacuum oven at 60 °C for 24 h.
[0039] (2) Activation: Soak the pretreated dandelion seeds in 0.1 mol·L -1 The activated dandelion seeds were heated to 100°C in a KOH solution and boiled for 10 h, and then dried in a vacuum oven at 60°C for 24 h.
[0040] (3) Carbonization: Argon was used as the shielding gas with a flow rate of 50 mL min -1 , set the tube furnace to 5℃·min -1 The heating rate was 1.5 ℃, the temperature was raised to 400℃, kept at this temperature for 1 hour, and then raised to 800℃ and kept at this temperature for another 1 hour. The carbonized material was ground in an agate mortar.
[0041] (4) Extraction: After the sample is carbonized, 150 mL of hydrochloric acid (molar concentration: 3.0 mol·L -1 ) and stirred with a magnetic stirrer for 1 h; then the sample was rinsed with deionized water until neutral (pH = 7.0), the supernatant was removed, and dried in a vacuum oven at 60 ° C for 24 h;
[0042] (5) After N nano powder (35-210 μm) and polytetrafluoroethylene were ultrasonically mixed (240 W) for 40 min (N nano powder: polytetrafluoroethylene = 8:1 is the optimal ratio), a mixed solution was obtained, the pretreated carbon felt was immersed in the mixed solution, taken out and dried at 60°C to obtain a 1-layer coated anode; 1-layer coated material was immersed in the mixed solution, taken out and dried at 60°C to obtain a 2-layer coated anode (the 2-layer coated material has excellent practical application performance). Under the corresponding treatment method, the thickness of 1 to 3 layers of coating can be obtained as shown in Table 1 and Table 2.
[0043] Table 11~3 layers of CS coated CF thickness data
[0044]
[0045] Table 2 Thickness data of 1 to 3 layers of N nanopowder coated CF
[0046]
[0047] It can be seen from Tables 1 and 2 that the amount of N nanopowder is lower at a smaller coating thickness, and there is a problem of excessive thickness and unchanged use at a larger coating thickness.
[0048] The pretreated carbon felt was cut into 2×4cm, 2×5cm, 2×6cm, 3×4cm, 3×5cm, and 3×6cm. After being coated with N nanopowder anode material, they were dried and immersed in anode liquid. The electrochemical properties, including CV curve, LSV, and Tafel, were measured using an electrochemical workstation. The results are shown in Figure 2. Figure 2 shown.
[0049] For the results obtained in Examples 1 and 2 Figure 1 , Figure 2 By comparison, it can be found that for the treated anode and cathode materials, as the area increases, the reducibility increases, the area enclosed by the CV curve also increases, and the conductivity increases; LSV is used to describe the limiting current density and the starting potential. Generally speaking, the greater the limiting current density, the higher the starting potential, the faster the rate of the electrochemical reaction, and the better the electrode performance. From the starting potential, as the area increases, the results of the LSV graph are almost the same. In the Tafel curve, as the area increases, the equilibrium potential shifts to the left and moves in the reverse direction, the electron transfer ability weakens, and the corrosion resistance is enhanced. The performance is carefully selected, and the standard of carbon felt is selected to be 3×6cm.
[0050] During the experiment, as the area increases, the internal resistance also increases, hindering the transfer of electrons. Moreover, since it is carbon felt, too large an area will lead to a weakening of the mechanical strength of the electrode and reduce the service life of the electrode. In summary, the usable area of 3×6 cm is the preferred usage area.
[0051] Example 3
[0052] This example is used to prepare the cathode material for the microbial battery device and briefly describes the assembly. The specific steps are as follows:
[0053] (1) preparing an acetic acid aqueous solution of a certain volume concentration, adding chitosan (molecular weight 10 kDa, light yellow), ferrosoferric oxide and copper iron oxide powder into the acetic acid aqueous solution in a ratio of 1:1:1, and stirring to obtain a metal-doped chitosan mixed solution (aqueous phase);
[0054] (2) 50 ml of liquid paraffin and 5 ml of Span-80 were stirred and mixed to obtain a mixed solution (oil phase); 25 ml of the metal-doped chitosan mixed solution was gradually added to the oil phase mixed solution, heated in a water bath and stirred to obtain a water-oil phase mixed solution;
[0055] (3) Add 0.7 ml of 5% glutaraldehyde aqueous solution to the water-oil mixed solution and react for 1 h; adjust the pH of the reaction solution to 10 and react for another 4 h;
[0056] (4) the reaction product is washed with acetone, anhydrous ethanol, and petroleum ether, filtered, and dried to obtain metal-doped chitosan microspheres;
[0057] (5) The metal-doped chitosan microspheres were mixed with KOH in a ratio of 1:2 and impregnated for 4 h, then dried and carbonized in a tube furnace at 850 °C for 3 h; and washed with deionized water until neutral.
[0058] (6) Ultrasonic mixing of the prepared metal-doped chitosan microsphere powder and polytetrafluoroethylene (metal-doped chitosan microsphere powder: polytetrafluoroethylene = 8:1 is the optimal ratio) to obtain a mixed solution, immersing the pretreated carbon felt in the mixed solution, taking out and drying at 60°C to obtain a 1-layer coated cathode; immersing the 1-layer coated material in the mixed solution, taking out and drying at 60°C to obtain a 2-layer coated cathode (the 2-layer coated material has excellent practical application performance).
[0059] The prepared cathode material (3×6 cm) was placed in the cathode chamber, ordinary carbon felt was used as the anode, cation and cathode liquids were added, the cathode was aerated, the anode was connected to the electrogenic bacteria, and the chamber was sealed to isolate oxygen.
[0060] The battery is connected to an external 1000Ω resistor, and its voltage is monitored in real time using the Rambo test system.
[0061] After the battery is started and runs stably, the maximum power density is 1356.2mW·m -2 , 180% higher than ordinary carbon felt.
[0062] Example 4
[0063] This embodiment is used to prepare a new anode material and improve the performance of a microbial fuel cell device. The specific steps are as follows:
[0064] (1) Pretreatment: Natural dandelion seeds (produced in Hebei Province, with high protein content) were soaked in acetone for 6 h to remove impurities such as surface oil and other dirt. They were then washed three times with deionized water and dried in a vacuum oven at 60 °C for 24 h.
[0065] (2) Activation: Soak the pretreated dandelion seeds in 0.1 mol·L -1The activated dandelion seeds were heated to 100°C in a KOH solution and boiled for 10 h, and then dried in a vacuum oven at 60°C for 24 h.
[0066] (3) Carbonization: Argon was used as the shielding gas with a flow rate of 50 mL min -1 , set the tube furnace to 5℃·min -1 The heating rate was 1.5 ℃, the temperature was raised to 400℃, kept at this temperature for 1 hour, and then raised to 800℃ and kept at this temperature for another 1 hour. The carbonized material was ground in an agate mortar.
[0067] (4) Extraction: After the sample is carbonized, 150 mL of hydrochloric acid (molar concentration: 3.0 mol·L -1 ) and stirred with a magnetic stirrer for 1 h; then the sample was rinsed with deionized water until neutral (pH = 7.0), the supernatant was removed, and dried in a vacuum oven at 60 ° C for 24 h;
[0068] (5) After N nanopowder (35-210 μm) and polytetrafluoroethylene are ultrasonically mixed (240 W) for 40 minutes (N nanopowder: polytetrafluoroethylene = 8:1 is the optimal ratio), a mixed solution is obtained, the pretreated carbon felt is immersed in the mixed solution, taken out and dried at 60°C to obtain a 1-layer coated anode; the 1-layer coated material is immersed in the mixed solution, taken out and dried at 60°C to obtain a 2-layer coated anode (the 2-layer coated material has excellent actual application performance).
[0069] The prepared anode material is placed in the anode chamber, ordinary carbon felt is used for the cathode, the cation and cathode liquids are added, the anode is connected to the electrogenic bacteria, the anode is sealed to isolate oxygen, and the cathode is aerated.
[0070] The battery is connected to an external 1000Ω resistor, and its voltage is monitored in real time using the Rambo test system.
[0071] After the battery is started and runs stably, the maximum power density is 1122.41mW·m -2 , which is 1.6 times that of carbon cloth.
[0072] The practical application results of the electrode materials in Examples 3 and 4 show that both carbon felt modified materials can greatly enhance the voltage. Therefore, if both are applied to the same microbial fuel cell device, the increase in voltage will be significant.
[0073] After the circuits are connected in parallel, the trend of the potential of the anode and cathode of the parallel stack changing with the current is slower than that of a single cell. Under the same external resistance conditions, the stack maintains a higher output voltage than a single cell, making the stack performance better than that of each single cell before parallel connection. This is mainly because after the parallel connection, the anodes of the two batteries are connected, and the electrons generated per unit time increase, causing the current in the circuit to increase.
[0074] Due to the reverse polarity phenomenon of series-connected batteries, parallel connection is chosen to increase the battery voltage.
[0075] For the microbial fuel cell operating device obtained in this embodiment, glucose is regularly added to the anode chamber in the early stage of startup to ensure that the microorganisms can grow and reproduce. After it gradually stabilizes, the anode liquid is regularly replaced and the cathode liquid is supplemented. Under the condition of ensuring that the anode nutrients are sufficient and the temperature is constant, the device can continuously and stably ensure that the bulb emits light.
[0076] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a microbial fuel cell, characterized in that: include, preparing cathode materials; preparing anode materials; The cathode material and the anode material are placed in the order of cathode and anode to form a circuit, thereby obtaining a microbial fuel cell; The anode material is prepared by coating N nanopowder on pretreated carbon felt; The cathode material is prepared by coating metal-doped chitosan microspheres on pretreated carbon felt, wherein the raw materials for preparing the metal-doped chitosan microspheres include chitosan, ferroferric oxide, and copper oxide, wherein the mass ratio of chitosan, ferroferric oxide, and copper oxide is 1:1:1; The pretreatment is to soak the carbon felt in a hydrogen peroxide solution, wash it and then soak it in hydrochloric acid to wash it until it is restored to neutrality; The pretreated carbon felt has a size of 3×6 cm.
2. The preparation method according to claim 1, characterized in that: The microbial fuel cell is maintained at an ambient temperature of 30-35°C.
Citation Information
Patent Citations
Microbial fuel cell anode and preparation method thereof and microbial fuel cell
CN108172852A